AL RAZ MUSLIM FASHION PRODUCTION MANAGEMENT STRATEGY IN FACING BUSINESS CHALLENGES DURING THE COVID 19 PANDEMIC ISLAMIC ECONOMIC PERSPECTIVE - Mohammad Rofiuddin; Muhajir Sulthonul Aziz (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
The COVID-19 pandemic is a deadly virus that has spread to almost every corner of the world. This makes all daily activities paralyzed, especially from an economic point of view, especially in the field of fashion. So it becomes a big challenge for the business world in dealing with economic conditions. Likewise with the Muslim fashion manufacturer Al Raz. How to face challenges in managing production during the Covid19 pandemic from 2020 until 2021. So this research is important to find out the production strategy in surviving the Covid19 pandemic and whether it is in accordance with Islamic law. The type of research used is a qualitative descriptive approach with primary and secondary data sources. The data collection technique is by interview and literature study while the research analysis is qualitative. From the results of the study it was concluded that Al Raz is not in accordance with Islamic law because the production results have transparent body parts. The workforce factor is applied by empowering residents around the work location, prioritizing spiritual values, and providing skills training to employees. The capital factor will also have an influence on profit, the profit presentation from Al Raz takes 25% of total production. The raw material factor is applied in the form of selecting halal raw materials. Organizational factors are not well coordinated, still in the family sphere. However, in carrying out cooperation both in terms of capital and the acquisition of raw materials is not in accordance with Islamic teachings. This condition can be demonstrated by cooperation using conventional banks and the wage system has not used the wage system in Islam.